Anticholinergic, antidiabetic and antioxidant activities of Anatolian pennyroyal (Mentha pulegium)-analysis of its polyphenol contents by LC-MS/MS. (January 2020) - Gülçin, İlhami; Gören, Ahmet C.; Taslimi, Parham; Alwasel, Saleh H.; Kılıc, Omer; Bursal, Ercan
Abstract: Methanol and water extracts of pennyroyal ( Mentha pulegium ) were evaluated for their antioxidant profiles by eight distinguished bioanalytical methods and for their inhibitory effects against enzymes linked to different diseases, namely acetylcholinesterase, butyrylcholinesterase, α-glycosidase and α-amylase. Additionally, the antioxidant properties of both extracts were determined and their polyphenolic compositions were evaluated by LC-MS/MS. For estimation of the antioxidant capacities of methanolic extract of pennyroyal (MEP) and water extract of pennyroyal (WEP); 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid radical (ABTS + ), 1, 1-diphenyl-2-picrylhydrazyl free radical (DPPH ), and N, N -dimethyl-p-phenylenediamine (DMPD + ) scavenging activities, Fe 3+ -2, 4, 6-tris(2-pyridyl)-s-triazine (TPTZ), Fe 3+, and Cu 2+ reducing assays were studied. The IC50 values of the MEP and WEP indicated that they were potent effective DPPH· (16.92 and 18.52 μg/mL), ABTS + (7.92 and 9.37 μg/mL) and DMPD + (36.02 and 38.94 μg/mL) scavengers, as well as acetylcholinesterase (AChE) (40.76 and 60 μg/mL), butyrylcholinesterase (BChE) (49.51 and 63.03 μg/mL), α-glycosidase (20.38 and 21.65 μg/mL) and α-amylase (23.11 and 36.47 μg/mL) inhibitors. Plant materials are potential sources for novel products in food and pharmaceutical applications. Also, biologically active compounds from plants have proven to be desirable in cosmetics, foods, and pharmaceuticals. This study clearly showed that both MEP and WEP had a broad screening of active compounds and phytochemicals. As a result of this abundant active ingredient, both extracts possessed antioxidant, anticholinergic and anti-diabetes properties. Highlights: Polyphenol contents of Mentha pulegium were analyzed by LC-MS/MS. Kaempferol-3-O-rutinoside was found the most abundan polyphnol in Mentha pulegium extracts. Anticholinergic and antidiabetic of Mentha pulegium was determined. Antioxidant activity of Mentha pulegium was performed using several bioassay.